Analisis Preferensi Mahasiswa di Salatiga Dalam Menentukan Jenis Kendaraan Online Gojek Menggunakan Metode Naïve Bayes - Christanto, Henoch Juli; Hiuredhy, Davin Kurnia; Dagha, Willyam Chrisna Umbu; Sutresno, Stephen Aprius; Dewi, Christine (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The development of technology in online transportation services like Gojek has a significant impact on meeting the mobility needs of modern society. The city of Salatiga, with many students from outside the island, has a considerable number of individuals without their own vehicles who prefer to use Gojek services. Therefore, research was conducted to analyze the preferences of students in Salatiga in determining the type of Gojek online transportation using the Naïve Bayes method. One hundred questionnaires from Salatiga students were collected, and the results yielded probability values for Gojek service preferences based on a combination of variables such as weather, load, destination, and time. It is evident from the probability values that weather and time variables play a crucial role in influencing users' decisions between using Go-Ride or switching to Go-Car. These results can provide guidance for Gojek in designing service innovations that are more responsive to user needs based on various specific factors.